Changes in antimicrobial susceptibility of commonly clinically significant isolates before and after the interventions on surgical prophylactic antibiotics (SPAs) in Shanghai - Wang,Su (2018)
Abstract Surveillances and interventions on antibiotics use have been suggested to improve serious drug-resistance worldwide. Since 2007, our hospital have proposed many measures for regulating surgical prophylactic antibiotics (carbapenems, third gen. cephalosporins, vancomycin, etc.) prescribing practices, like formulary restriction or replacement for surgical prophylactic antibiotics and timely feedback. To assess the impacts on drug-resistance after interventions, we enrolled infected patients in 2006 (pre-intervention period) and 2014 (post-intervention period) in a tertiary hospital in Shanghai. Proportions of targeted pathogens were analyzed: methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus spp. (VRE), imipenem-resistant Escherichia coli (IREC), imipenem-resistant Klebsiella pneumoniae (IRKP), imipenem-resistant Acinetobacter baumannii (IRAB) and imipenem-resistant Pseudomonas aeruginosa (IRPA) isolates. Rates of them were estimated and compared between Surgical Department, ICU and Internal Department during two periods. The total proportions of targeted isolates in Surgical Department (62.44%, 2006; 64.09%, 2014) were more than those in ICU (46.13%, 2006; 50.99%, 2014) and in Internal Department (44.54%, 2006; 51.20%, 2014). Only MRSA has decreased significantly (80.48%, 2006; 55.97%, 2014) (p < 0.0001). The percentages of VRE and IREC in 3 departments were all <15%, and the slightest change were also both observed in Surgical Department (VRE: 0.76%, 2006; 2.03%, 2014) (IREC: 2.69%, 2006; 2.63%, 2014). The interventions on surgical prophylactic antibiotics can be effective for improving resistance; antimicrobial stewardship must be combined with infection control practices.